Integrative model as a value creation tool in the customs administration system - M. V. Boykova (Вестник университета)
The current system of customs administration provides a solution to complex economic and social problems. It is focused on the formation of value and consumer utility within the framework of the functions performed. In this regard, the quality of such a system is of particular importance. The article investigates the application of the value approach to the customs administration system. The paper carries out the analysis of the value chain formation. The study defines the approaches to the value assessment for each subject of the customs administration system. The paper proposes an integrative model that contributes to increasing the value of customs services in the system of service-oriented customs administration. The author draws conclusions about the role and significance of the value of each subject of the customs administration system in the formation of public value. The presented research is based on the concept of a holistic-evolutionary approach.